PENGARUH BAURAN ECERAN (RETAILING MIX) TERHADAP CITRA YANG BERLAKU (CURRENT IMAGE) PADA ALFAMART DUSTIRA CIMAHI - Jatmika, Lungguh; Roslina, Nita Yura (Majalah Bisnis & IPTEK, 2021)
This study aims to determine how the effects of retail mix of brand image. This research is a quantitative research with descriptive and verifikatif data analysis. Technique of sample determination by using accidental sampling counted 30 respondents. The results showed that the retail mix entered in both categories and brand image entered in either category. The effect of retail mix on brand image amounted to 43.56%. It is stated that the formation of the current on Alfamart Dustira Cimahi also determined by other factors of 56.44% which is not examined in this study. Keywords: retail mix, brand image.